Rancang Bangun Sistem Pendingin Air Nutrisi Berbasis Peltier untuk Optimasi Pertumbuhan Tanaman Hidroponik - Saputra, Oki; Abdullah, Sirajuddin H.; Sumarsono, Joko; Priyati, Asih; de Side, Gagassage Nanaluih; Putra, Guyup Mahardhian Dwi; Setiawati, Diah Ajeng; Amaliah, Wenny; Dewi, Endang Purnama; Nurrohman, Reza Kusuma; Zamzami, Muhammad Ilham; Sani, Nurwan (LPPM Universitas Mataram, 2025)
High ambient temperatures inside tropical greenhouses can significantly raise nutrient solution temperatures in vertical hydroponic systems, disrupting nutrient uptake and reducing plant productivity. This study focuses on the design and development of a nutrient cooling system (chiller) using two TEC1-12706 thermoelectric modules (Peltier) arranged in series to enhance heat dissipation performance. The nutrient solution is pumped from the reservoir to the cooling chamber using a 12 V DC pump and recirculated in a closed-loop configuration. The chiller system is fully automated, controlled by two DH48S digital timers operating simultaneously: one activates Peltier 1, while the other controls Peltier 2 via the NC output (5 minutes) and the pump via the NO output (30 seconds), enabling alternating programmed cooling and circulation. The entire chiller unit is active only from 08:00 to 18:00 WITA using a KG316T programmable timer, corresponding to peak thermal stress hours inside the greenhouse. Results showed that despite greenhouse temperatures reaching up to 39.4 °C with relative humidity dropping to 47.6%, the chiller system maintained nutrient solution temperatures within the optimal 27–30 °C range. This design proved effective in reducing and stabilizing nutrient temperature under high heat microclimates. With its simple, automated, and energy-efficient architecture, the chiller system offers a promising solution for small-scale vertical hydroponics and greenhouse-based urban farming in tropical regions.